Deskriptivna rekonstrukcija pogajanj za pravno zavezujoči sporazum o gozdovih v Evropi - Leban, Vasja (Teorija in praksa, 2020)
This article reconstructs and analyses the multilateral negotiation process during which parties discussed the content of a Legally Binding Agreement on Forests in Europe. Negotiations may be thought of as a social interaction that takes place within existing structural and cultural conditions. The negotiating actors choose an integrative strategy and corresponding tactics. In order to successfully conclude the negotiations, two topics must be resolved, namely the United Nations' role and the position of the secretariat. The negotiations offered many solutions, especially due to the change in cultural conditions, although the area of possible agreement was too narrow for the negotiations to come to a successful conclusion
Keywords: analiza vsebine sporazuma; content analysis; Europe; Evropa; FOREST EUROPE; Forestry; forestry legislation; Gozdarstvo; international process; legally binding agreement; Legislation; mednarodni proces; pravno zavezujoči sporazum; Zakonodaja